Pedagogical Reasoning Guru PAI dalam Mengintegrasikan Ilmu Agama dan Ilmu Sosial - Wahidah, Nur; Nursyam, Nursyam; Cholil, Mufida (Journal of Islamic Education and Pedagogy, 2026)
This study examines the pedagogical reasoning of Islamic Religious Education (PAI) teachers in integrating religious knowledge and social sciences at MA Miftahul Huda Banyuwangi. The integration of knowledge is a crucial issue in Islamic education, particularly in responding to the dichotomy between religious and general sciences that still persists in learning practices. This research aims to analyze how PAI teachers plan, implement, and evaluate learning by integrating Islamic teachings with social realities through pedagogical reasoning processes. This study employed a qualitative case study approach. Data were collected through in-depth interviews, classroom observations, and document analysis involving PAI teachers, students, and school leaders. The findings indicate that teachers’ pedagogical reasoning is reflected in five interconnected stages: comprehension of subject matter, transformation of content, instructional implementation, evaluation of learning, and reflective practice. Through this process, teachers are able to contextualize Islamic teachings with social issues such as tolerance, social justice, and community life. This study recommends strengthening teachers’ pedagogical reasoning competencies through continuous professional development to support integrative Islamic education.